Development and Implementation of Quality Assurance According to GMP Guidelines in Lebanese Pharmaceutical Companies - Yassin, Nour (Technium Social Sciences Journal, 2022)
The quality of pharmaceuticals has always been a concern to the World Health Organization (WHO) from the beginning its inception. Good Manufacturing Practice (GMP) is an important part of a comprehensive system of quality assurance (QA) for both manufacturers and the government. In Lebanon, and since its application, many challenges faced the implementation of the QA program according to GMP guidelines. Yet, this program has been successfully implemented in the Lebanese pharmaceutical industry supported by the Lebanese Ministry of Public Health (MOPH), and the commitment of the national GMP committee, in addition to the involvement of the public and private pharmaceutical sectors. The main objective of this study is to evaluate the implementation of the QA program according to GMP guidelines by selected Lebanese pharmaceutical companies. A descriptive analytical study was conducted between August-November of 2018, using a questionnaire that was administered to the quality departments of 10 Lebanese pharmaceutical companies. Finding showed that all these companies were implementing the QA programs according to GMP guidelines (100%), where 60% of their quality managers are experienced in GMP guidelines for more than 6 years. Further, 50% of these companies were applying QA program according GMP guidelines since more than 6 years, and 80% of them are formulating their programs using all the quality tools of the international GMP standards. Moreover, 80% of them are establishing awareness toward the implementation of GMP guidelines through training by internal expertise and external consultants. On the other hand, the implementation cost was the most important challenge faced by 60% of these firms. Finally, all companies are profiting by an increase in efficacy and efficiency, better product quality, and decrease in defects due to the implementation of the GMP guidelines. All the Lebanese pharmaceutical companies are working toward developing their program to meet the international standards, yet, they still need governmental support to spread and compete around the world.